2016
DOI: 10.2139/ssrn.2940724
|View full text |Cite
|
Sign up to set email alerts
|

Local Institutional Structure and Clientelistic Access to Employment: The Case of MGNREGS in Three States of India

Abstract: This work is a contribution, first, toward measuring and characterizing some features of rural clientelistic institutions and then toward exploring its impact on household access to an employment scheme (MGNREGS programme in India). We focus on patron-client relationship and the presence and intensity of that: i.e., on the nature and distribution of power in the rural society based on the data on personalized day-today interactions of the households residing in a village in economic, social and political spher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 55 publications
1
7
0
Order By: Relevance
“…Estimates at these alternate thresholds are either smaller in magnitude and not significantly different from zero, or the estimated coefficients are positive (as opposed to the negative estimates found at the samras threshold). Overall, these results appear to be consistent with a theory of clientelism, as prior research has shown that most elites in Indian villages are either upper caste or OBC whereas most clients are SC, ST or OBC (Bhattacharya et al , 2016). I discuss how clientelism may explain the regressive targeting results documented here in more detail in Section 4.5.…”
Section: Workfare Employment the Mahatma Gandhi National Rural Employment Guaranteesupporting
confidence: 85%
See 3 more Smart Citations
“…Estimates at these alternate thresholds are either smaller in magnitude and not significantly different from zero, or the estimated coefficients are positive (as opposed to the negative estimates found at the samras threshold). Overall, these results appear to be consistent with a theory of clientelism, as prior research has shown that most elites in Indian villages are either upper caste or OBC whereas most clients are SC, ST or OBC (Bhattacharya et al , 2016). I discuss how clientelism may explain the regressive targeting results documented here in more detail in Section 4.5.…”
Section: Workfare Employment the Mahatma Gandhi National Rural Employment Guaranteesupporting
confidence: 85%
“…28 As Appendix Table A.4 shows, over half of all GP candidates are drawn from farm and business owning households. Bhattacharya et al (2016) also document that on average these households tend to be richer.…”
Section: Political Selectionmentioning
confidence: 81%
See 2 more Smart Citations
“…The reduction in political competition ushers in younger, more educated representatives, but does not significantly increase the proportion of female politicians. I also test for effects on occupation, and find that the grant does not increase the proportion of candidates from farming and business, which are indicative of elite status within Indian villages (Bhattacharya et al 2016). Therefore, even though qualitative evidence suggests that the local elite have a greater say in consensus-based elections, I find suggestive evidence that they do not crowd themselves into political office.…”
Section: Political Selectionmentioning
confidence: 75%